Arabidopsis Novel Microgametophyte Defective Mutant 1 Is Required for Pollen Viability via Influencing Intine Development in Arabidopsis - Mi, Limin; Mo, Aowei; Yang, Jiange; Liu, Hui; Ren, Ding; Chen, Wanli; Long, Haifei; Jiang, Ning; Zhang, Tian; Lu, Pingli (Frontiers in Plant Science, 2022)
In flowering plants, pollen intine is indispensable for male fertility. But, the knowledge in developmental regulation of intine formation still remains largely unknown. Here, we identified a positive regulator, ARABIDOPSIS NOVEL MICROGAMETOPHYTE DEFECTIVE MUTANT 1 (AtNMDM1), which influences male fertility by regulating intine formation. AtNMDM1, encoding a pollen nuclei localized protein, was highly expressed in pollen at stages 10-12. Both the mutations and knock-down of AtNMDM1 resulted in pollen defects and significantly lower seed-setting rate. Genetic transmission analysis indicated that AtNMDM1 is a microgametophyte lethal gene. Calcofluor white staining revealed that abnormal cellulose distribution was appeared in aborted pollen. Ultrastructural analyses showed that the abnormal intine rather than exine led to pollen abortion. We further found that most significantly downregulated genes were enriched in category of cell wall modification by transcriptome analysis. Notably, two categories of genes, ARABINOGALACTAN PROTEINS (AGPs) and PECTIN METHYLESTERASES (PMEs) were greatly reduced, which were associated with pollen intine formation. In addition, we also identified another regulator AtNMDM2, which interacted with AtNMDM1 in the pollen nuclei. Taken together, we identified a novel regulator AtNMDM1 that affected cellulose distribution in intine by regulating intine-related genes expression and provided insights for the molecular mechanisms of pollen intine development.